A Developing Model of Utilizing and Producing Galam (Melaleucaleucadendron) as A Natural Wood Preservative - Siti Hamidah; Trisnu Satriadi; Badaruddin Badaruddin; Violet Burhanuddin (Journal of Wetlands Environmental Management, 2015)
This research aims to get both the active chemical compounds of galam’swood vinegar which functions as antifungi and anti-termite usage and the process or factors influence it. Another purpose of the research is to find how effective the active compounds are toward wood destroyer organisms, either termite or fungus. Anti-termite assay is done by using a method of the mortal percentage of termites in sort of Cryptotermes cynocephalus Light and a method of growth inhibition of Schizopyllum commune fungus by wood vinegar for antifungi assay. To find the influence within the treatment of wood vinegar production process (the raw material condition and distillation), wood vinegar concentration level concerning with the active compounds of antifungi and anti-termite, each of treatments is analyzed using statistical analysis with CRD. Wood vinegar is a natural organic liquid resulting from the condensation of smoke in the process of making charcoal. Generally, the result shows that galam’s wood vinegar have a potential used as natural wood preservative material. For this kind of utility, the vinegar can either be spontaneously used or be reproduced by a distillation process with 50% concentration. Galam’swood vinegar contains some components, namely phenolic, acid and carbonyl.